Makna Sumpah Pemuda bagi Pelajar MAN 2 Surakarta: Analisis Impresi Buku Teks Sejarah SMA Kelas XI Kurikulum 2013 Revisi - Novia Faqihatun Nikmah (Universitas Negeri Malang, 2021)
This study aims to determine the conclusions of the analysis and conditions of the Youth Pledge material in the Indonesian History textbook for SMA class XI semester 1 of the 2013 Revised 2017 curriculum used in learning at MAN 2 Surakarta. Another goal is to find out the understanding of students in interpreting a Youth Pledge after learning related to youth oath material in the Indonesian History textbook for SMA class XI semester 1 of the 2013 Revision of the 2017 curriculum. Indonesia SMA class XI semester 1 2013 Revised 2017 curriculum in this study in compiling articles using qualitative methods. The source data are collected from the results of filling out a questionnaire that has been distributed to students of MAN 2 Surakarta via google form. The result is that the completeness of the Youth Pledge material in the book is quite good, but various deficiencies can also be seen such as a lack of understanding of some students towards the Youth Pledge material and a lack of awareness in speaking Indonesian according to the rules of communication.Penelitian ini bertujuan mengetahui kesimpulan dari analisis dan kondisi dari materi Sumpah Pemuda didalam Buku teks Sejarah Indonesia SMA kelas XI semester 1 kurikulum 2013 Revisi 2017 yang digunakan dalam pembelajaran di MAN 2 Surakarta. Adapun tujuan lain yaitu mengetahui pemahaman siswa dalam memaknai sebuah Sumpah Pemuda setelah adanya pembelajaran yang berkaitan dengan materi sumpah pemuda didalam Buku teks Sejarah Indonesia SMA kelas XI semester 1 kurikulum 2013 Revisi 2017. Juga untuk mengetahui sikap siswa setelah mempelajari makna sumpah pemuda dalam Buku teks Sejarah Indonesia SMA kelas XI semester 1 kurikulum 2013 Revisi 2017. didalam penelitian ini dalam menyusun artikel menggunakan metode kualitatif. Yang data-data sumber dikumpulkan dari hasil pengisian angket yang telah disebar pada siswa MAN 2 Surakarta melalui google form. Hasilnya pun kelengkapan materi Sumpah Pemuda didalam buku sudah cukup baik, tetapi berbagai kekurangan juga terlihat adanya seperti kurangnya pemahaman sebagian siswa terhadap materi Sumpah Pemuda dan kurangnya kesadaran dalam berbahasa Indonesia yang sesuai kaidah dalam berkomunikasi.